New Laws Related to Oil Extraction Rights and Social Safeguards are Affecting Socio-Economic Well Being of Communities in the Albertine Graben - Ivan Lwanyaga; Ricardo Saaverdra; Charles Edaku (International Journal on Economics, Finance and Sustainable Development, 2022)
The study was carried out in order to assess how the new laws related to extraction rights and social safeguards are affecting socioeconomic well-being of communities in the Albertine Graben. The study concentrated both on primary and secondary data. The primary survey was critical component of the study as it would yield crucial data on the oil governance and socio-economic well-being of communities in the Albertine Graben (Respondents), and officials from the ministry of lands zonal office, Officials from international oil companies, Local government officials, Political/religious leaders, Local council members, Bunyoro kingdom officials and Community members. The study was conducted in four districts on Hoima, Buliisa Kikube, and Kakumiro in the Albertine Graben region; where a sample of 158 respondents was selected from these districts. Districts were selected using judgmental sampling and 158 respondents were selected using simple random and purposive sampling. Parameters on the basis of which research questions were formed to investigate the new laws related to extraction rights and social safeguards are affecting socioeconomic well-being of communities in the Albertine Graben. From the field findings, it was found out that there was need for the employment of the local people and from across all districts in the Abertane graben, environmental protection was embraced through a forestation, frame works for effective revenue collection from oil companies are said to have been put in place, communities in the Albertinee graben have been secured from dangers of oil spilling and this has been done through compensation of all communities that are found where the pipeline was being constructed. Existing and new measure of controlling corruption from government officials have tightened up, monitoring of exploration is being observed wholeheartedly, sensitization of community awareness on danger of oil wastes has been carried out in all Abertine graben communities and lastly there has been establishment of cumulative effect assessment systems. In regard to Land Laws, Ugandan government and all the stakeholders involved needs to reform its land policy to ensure that every Ugandan can access the land or can ‘legally’ own the land they live in by providing them with required documents to prove their ownership. In addition, there is need for workers in Uganda to organize and demand their social- economic rights and accountability from the government.